PENGARUH UKURAN KAP, OPINI AUDIT, KESULITAN KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP PERGANTIAN KANTOR AKUNTAN PUBLIK PADA PERUSAHAAN MANUFAKTUR SEKTOR MAKANAN DAN MINUMAN (Studi Empiris pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Azalia, Rahmanita; Zirman, Zirman; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study examines to the influence of KAP size, audit opinion, financial distress, and tclient size against the auditor switching. The population was the food and beverage sector of manufactur companies listed on the BEI in the period 2013-2015, and the sample in this study with certain criteria, so that it obtained 12 companies as samples. The data collected with the financial report of the food and beverage sector of manufactur companies listed on the BEI in the period 2013-2015. The method of analysis used is multiple logistic regression. The independent variable in this study is the KAP size, audit opinion, financial distress, and client size using variable dummy. While the dependent variable is the auditor switching is also measured using a variable dummy. Based on the results of the analysis indicate that the KAP size has impact on the auditor switching, audit opinion has impact on the auditor switching, and the financial distress and client size no impact on the auditor switching. The most dominant variable influencing the auditor switching is KAP size because it has a beta value of 0.075 standard coefficient.Keywords : KAP size, audit opinion, finacial distress, client size, auditor switching.